2022
DOI: 10.1002/joc.7772
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of precipitation and temperature to multiscale drought variations over Asia: Dependence on the time scale

Abstract: Drought variations are determined by precipitation and temperature changes. The present study examines the relative contributions of precipitation and temperature to temporal variations of short-term, medium-term and long-term droughts over Asia. This is accomplished by comparing (a) the variations of Standardized Precipitation Index (SPI) and Standardized Precipitation Evapotranspiration Index (SPEI) that extend over 3, 9 and 24 months (i.e., shortterm, medium-term and long-term droughts, respectively) and (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Focused on the multi‐year drought events over Asia, Zhang et al. (2022) found that the contribution of temperature to the variations of the north‐south dipole pattern of short‐term drought events is higher than precipitation. While for long‐term drought events, the relative contribution of precipitation and temperature depends upon the locations of drought events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focused on the multi‐year drought events over Asia, Zhang et al. (2022) found that the contribution of temperature to the variations of the north‐south dipole pattern of short‐term drought events is higher than precipitation. While for long‐term drought events, the relative contribution of precipitation and temperature depends upon the locations of drought events.…”
Section: Introductionmentioning
confidence: 99%
“…Their results revealed that precipitation deficit was largely responsible for producing such an extreme drought event, but high temperature also played an important role in exacerbating drought severity. Focused on the multi-year drought events over Asia, Zhang et al (2022) found that the contribution of temperature to the variations of the north-south dipole pattern of short-term drought events is higher than precipitation. While for long-term drought events, the relative contribution of precipitation and temperature depends upon the locations of drought events.…”
mentioning
confidence: 99%